efectuati. {46-[26:2+(18-6•2):(4•2-5)]•3}•(15-10)
Răspunsuri la întrebare
Răspuns de
2
...............................................................
Anexe:
Răspuns de
0
{ 46 - [ 26 : 2 + ( 18 - 6 × 2 ) : ( 4 × 2 - 5 ) ] × 3 } × ( 15 - 10 ) =
{ 46 - [ 13 + ( 18 - 12 ) : ( 8 - 5 ) ] × 3 } × 5 =
[ 46 - ( 13 + 6 : 3 ) × 3 ] × 5 =
[ 46 - ( 13 + 2 ) × 3 ] × 5 =
( 46 - 15 × 3 ) × 5 =
( 46 - 45 ) × 5 =
1 × 5 = 5
{ 46 - [ 13 + ( 18 - 12 ) : ( 8 - 5 ) ] × 3 } × 5 =
[ 46 - ( 13 + 6 : 3 ) × 3 ] × 5 =
[ 46 - ( 13 + 2 ) × 3 ] × 5 =
( 46 - 15 × 3 ) × 5 =
( 46 - 45 ) × 5 =
1 × 5 = 5
Alte întrebări interesante
Informatică,
8 ani în urmă
Studii sociale,
8 ani în urmă
Istorie,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă